PENGARUH WAKTU PEMASAKAN PADA PANCI BERTEKANAN TERHADAP KELUNAKAN TULANG IKAN BANDENG - , Sri Murtono, S.Pd, Dr-Ing. Ir. Sihana ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research was done intent to look for effect of cooking time in the pressure cooker to bone softness. Reason title elect on observational it was caused haven't available bone softness quality uniformity soft spine milkfish that circulated at society. This research was done on time variation 60 minutes, 75 minutes and 90 minutes, at temperature 121 0 C worked pressure 0,85 kg / cm2. The raw material that was used milkfish with age 120 until 123 days and weight 270 until 275 grams tail each. There was even each cooking conduct process needs 3 milkfish with looped as much 3 times. As standard comparator softness of bone was presto milkfish from Juana Semarang. This research result prove that is influence which significant among cooking time to softening of bone on the soft spine milkfish makings processes. cooking up to 60 minutes, 75 minutes and 90 minutes with temperature 121 0 C at worked pressure 0,85 kg / cm2 to produce softness bone was 0,4971 kg / mm 2 , 0,3360 kg / mm 2 and 0,1566 kg / mm2, meanwhile it was relative softness in a row 1/21,6, 1/32,5 and 1/68,5.